Performance of an adaptive compander in wireless mobile communication systems. (23rd May 2019) - Beena, A.O.; Pillai, Sakuntala S.
The most popular technique used for high data rate services in 4G scenario is MIMO-OFDM. Space-time block codes have been recommended for high diversity gain in MIMO communication systems. Due to comparatively simpler design and less decoding complexity orthogonal STBCs are very attractive. In this paper, we propose a novel adaptive companding method for peak to average power ratio reduction in IEEE 802.16 standards used in 4G wireless mobile communications with orthogonal space time block coded MIMO-OFDM systems. This is obtained by fixing compander parameters independently for statistically unrelated symbols in OFDM waveform and according to the features of input symbols. The bit error rate performance analysis of the proposed system under Rayleigh fading MIMO channel conditions has also been presented. Simulation results showed that the proposed method performs better for a given PAPR preset value and a slight improvement in the BER performance was observed over fixed compander.